Heat Transfer, Volume 2 2006
DOI: 10.1115/imece2006-15120
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Evaporation Heat Transfer in Sintered Copper Wicks With Microgrooves

Abstract: This paper presents an experimental study on the parameters that determine the thermal performance of sintered copper wicks with longitudinal micro grooves for heat pipe applications. The grooves, which provide passages to vent vapor, have a width in a range from 150 μm to 500 μm. The copper powder used here has a nominal diameter of 50 μm, which produces an effective pore radius of approximately 13 μm. The main wicks composed of pores and grooves present characteristics of bi-dispersed wick structures. Unlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Due to this enhancement mechanism, a 3 mm thick microgrooved wick structure exhibited a dryout heat flux of 350 W/cm 2 , compared to 0.5 mm and 3 mm thick monoporous wick structures that dried out soon after boiling incipience at or below 100 W/cm 2 [39]. This dryout heat flux of 100 W/cm 2 is lower than other monoporous sintered wicks in the literature [35,37] was likely due to the extremely small constituent particle size (13 μm effective pore radius).…”
Section: Efficient Liquid Feeding and Vapor Extraction Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this enhancement mechanism, a 3 mm thick microgrooved wick structure exhibited a dryout heat flux of 350 W/cm 2 , compared to 0.5 mm and 3 mm thick monoporous wick structures that dried out soon after boiling incipience at or below 100 W/cm 2 [39]. This dryout heat flux of 100 W/cm 2 is lower than other monoporous sintered wicks in the literature [35,37] was likely due to the extremely small constituent particle size (13 μm effective pore radius).…”
Section: Efficient Liquid Feeding and Vapor Extraction Featuresmentioning
confidence: 99%
“…Further testing showed that 500 μm grooves outperform narrower 150 μm grooves that tend to remain partially filled with liquid. This liquid poses an additional resistance to vapor removal, as evidenced by liquid expulsion from the wick structure observed at higher heat fluxes [39].…”
Section: Efficient Liquid Feeding and Vapor Extraction Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several modifications to traditional monoporous wicks have been proposed in prior work [12][13][14][15][16] to improve the dryout heat flux and to decrease the thermal resistance of the wick structure to meet the cooling requirements for ultra-high heat flux applications. Semenic and Catton [12] compared the critical heat flux (CHF) of monoporous and biporous wicks (wicks with two different pore sizes) using water as the working fluid, under sub-atmospheric saturation pressure (< 13 kPa) conditions and reported high CHF values of 520 W/cm 2 and 990 W/cm 2 at superheats of 50 °C and 147 °C for 800 μm and 3000 μm thick biporous wicks, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, thick biporous wicks may not find practical use due to the high wick resistance and the high resulting wall superheat. Zhao and Chen [13] investigated the thermal performance of sintered copper wicks with microgrooves in the direction of liquid flow of widths ranging from 150-500 μm. Compared to a randomly distributed pattern of vapor exit pathways in biporous wicks, microgrooves provided aligned passages for vapor to exit the wick, and extended the CHF by as much as 350% compared to monoporous wicks.…”
Section: Introductionmentioning
confidence: 99%